A pulmonary artery dissection in infant. Issue 6 (4th March 2022) - Wen, Yang; Jin, Mei; Yang, Zhengbing
Abstract : Figure l shows echocardiography, A is the mixed echo mass from pulmonary artery to bifurcation and in left pulmonary artery, with a size of about 31.9mmx15.7mm; B is the CDFI image in the mass, showing a few spot like blood flow signals in the mass.